The post(-)colonial Arab city. Issue 2 (3rd May 2020) - Laurie, Emma; Philo, Christopher
ABSTRACT: Research from the 1980s by Ronan Paddison, Allan Findlay and colleagues on 'the post-colonial city' and 'the Arab city' is examined. Distinguishing between 'post-colonial' (as periodization) and 'postcolonial' (as critique), the paper traces how elements of the latter permeated what Paddison and colleagues claimed about the former. A sensitivity to urban 'models', histories and geographies beyond the Global North was evident, anticipating subsequent postcolonial moves to engage fully with the possibilities of multiple 'other' urban trajectories, lives, plans and capacities for change. It is also suggested that, inspired by Janet Abu-Lughod, Paddison and colleagues were working towards a postcolonial 'comparative urbanism'.